Optimal monetary policy under bounded rationality - Jonathan Benchimol; Lahcen Bounader (Bank of Finland, 2018)
Optimal monetary policy under discretion, commitment, and optimal simple rules regimes is analyzed through a behavioral New Keynesian model. Flexible price level targeting dominates under discretion; flexible inflation targeting dominates under commitment; and strict price level targeting dominates when using optimal simple rules. The optimality of a particular regime is found to be independent of bounded rationality and only regime 's stabilizing properties condition its hierarchy. For every targeting regime, the policymaker 's knowledge of agents' myopia is decisive in terms of policy reactions. Welfare evaluation of different targeting regimes reveals that bounded rationality is not necessarily associated with decreased welfare. Several forms of economic inattention can increase welfare.
URN:NBN:fi:bof-201804191453
Keywords: C53; E37; E52; D01; D11; 330